Objectively determined physical activity and adiposity measures in adult women: A systematic review and meta-analysis - Lu, Yining; Wiltshire, Huw D.; Baker, Julien S.; Wang, Qiaojun; Ying, Shanshan; Li, Jianshe; Lu, Yichen (Frontiers in Physiology, 2022)
The prevalence of adiposity is increasing among adult women. Although emerging evidence suggest that all patterns of heightened physical activity (PA) are important to benefit adiposity, the relationship between objectively assessed intensities of PA and adiposity in women has not yet been assessed. Therefore, this systematic review and meta-analysis aims to qualitatively synthesize and quantitatively assess the evidence for any relationship between objectively measured PA and a wide range of adiposity indicators to guide PA prescription in adult women. Four databases (PubMed, Web of Science, Scopus, and the Cochrane library) were searched for eligible studies. 35 studies were included (25 observational and 10 interventional studies), with a total of 9176 women from 20 countries included. The overall pooled correlation for random effects model (n = 1 intervention and n = 15 cross-sectional studies) revealed that the total volume of physical activity (TPA) was moderately associated with percentage body fat (%BF) (r = -0.59; 95% CI: -1.11, -0.24; p=0.003). There was a weak but significant association between MVPA with body mass index (BMI), waist circumference (WC), and visceral adiposity. Daily steps were significantly associated with BMI, %BF, WC, and fat mass, with the strongest association with %BF (r = -0.41; 95% CI: -0.66, -0.19; p<0.001). Walking programs resulting in increasing daily steps only had a significant effect on WC (SMD=-0.35; 95% CI: -0.65, -0.05; p=0.02). Overall, objectively determined PA in terms of steps, TPA and MVPA were favorably associated with adiposity outcomes. The improvement in adiposity can be achieved by simply accumulating more PA than previously and adiposity is more likely to be benefited by PA performed at higher intensity. Nonetheless, these results should be interpreted with caution as there were a small number of studies included in the meta-analysis and the majority of studies included utilized cross-sectional designs.